Fhenomenology of contemporay design - de Moraes, Dijon (DAT Journal, 2020)
This paper offers a reflection on the theme of “Contemporary Design Phenomenology”. It presents the challenges for the design in the open field, fuzzy and diffuse, where he demonstrates that the constant changes in scenarios and the fluidity of boundaries between art and design have created a fragile and uncertain terrain for design teaching in the 21st century.